Immunomodulatory steroids, in particular the hemihydrate of 16.alpha.[bromoepiandrosterone - CLARENCE NATHANIEL AHLEM; KRUPAKAR PAUL THADIKONDA; CHRISTOPHER L. READING; LUIS DANIEL DOS ANJOS DE CARVALHO; RUSSELL NEIL VERNON; JAMES MARTIN FRINCKE; HEGGIE, WILLIAM PRENDERGAST, PATRICK T (2003)
The invention provides compositions comprising formula 1 steroids, e.g., 16alpha-bromo-3beta-hydroxy-5alpha-androstan-17-one hemihydrate and one or more excipients, typically wherein the composition comprises less than about 3% water. The compositions are useful to make improved pharmaceutical formulations. The invention also provides methods of intermittent dosing of steroid compounds such as analogs of 16alpha-bromo-3beta-hydroxy-5alpha-androstan-17-one and compositions useful in such dosing regimens. The invention further provides compositions and methods to inhibit pathogen (viral) replication, ameliorate symptoms associated with immune dysregulation and to modulate immune responses in a subject using certain steroids and steroid analogs. The invention also provides methods to make and use these immunomodulatory compositions and formulations.